The Association of Functional Status with Mortality and Dialysis Modality Change: Results from the Peritoneal Dialysis Outcomes and Practice Patterns Study (PDOPPS). Issue 2 (March 2019) - Tennankore, Karthik; Zhao, Junhui; Karaboyas, Angelo; Bieber, Brian A.; Robinson, Bruce M.; Morgenstern, Hal; Jassal, S. Vanita; Finkelstein, Fredric O.; Kanjanabuch, Talerngsak; Cheawchanwattana, Areewan; Pisoni, Ronald L.; Sloand, James A.; et al.
Background: Little is known about the prevalence of functional impairment in peritoneal dialysis (PD) patients, its variation by country, and its association with mortality or transfer to hemodialysis. Methods: A prospective cohort study was conducted in PD patients from 7 countries in the Peritoneal Dialysis Outcomes and Practice Patterns Study (PDOPPS) (2014 – 2017). Functional status (FS) was assessed by combining self-reports of 8 instrumental and 5 basic activities of daily living, using the Lawton-Brody and the Katz questionnaires. Summary FS scores, ranging from 1.25 (most dependent) to 13 (independent), were based on the patient's ability to perform each activity with or without assistance. Logistic regression was used to estimate the odds ratio (OR; 95% confidence interval [CI]) of a FS score < 11 comparing each country with the United States (US). Cox regression was used to estimate the hazard ratio (HR; 95% CI) for the effect of a low FS score on mortality and transfer to hemodialysis, adjusting for case mix. Results: Of 2, 593 patients with complete data on FS, 48% were fully independent (FS = 13), 32% had a FS score 11 to < 13, 14% had a FS score 8 to < 11, and 6% had a FS score < 8. Relative to the US, low FS scores (< 11; more dependent) were more frequent in Thailand (OR = 10.48, 5.90 – 18.60) and the United Kingdom (UK) (OR = 3.29, 1.77 – 6.08), but similar in other PDOPPS countries. The FS score was inversely and monotonically associated with mortality but not with transfer to hemodialysis; the HR, comparing a FS score < 8 vs 13, was 4.01 (2.44 – 6.61) for mortality and 0.91 (0.58 – 1.43) for transfer to hemodialysis. Conclusion: Regional differences in FS scores observed across PDOPPS countries may have been partly due to differences in regional patient selection for PD. Functional impairment was associated with mortality but not with permanent transfer to hemodialysis.